MEDICO-DEMOGRAPHIC SITUATION IN THE REPUBLICS OF CHECHNYA AND INGUSHETIA IN 2005-2010 - P. M. Evloeva ("Paediatrician" Publishers LLC, 2012)
Political and socio-economical destabilization, military conflicts, lack of infrastructure and massive migratory movements formed a current medico-demographic situation in the Republics of Chechnya and Ingushetia: the fertility and birth rates here are very high and exceeds twice the same figures all over the Russian Federation. At the same time the infant mortality and feto-infantile losses rates are also very high. The high fertility leads to overpopulation, low per capita income, worsening of somatic and reproductive women's and children's health and consistent increase of reproductive losses. The aging of fertility (in the Republic of Ingushetia) and the low level of education (which is typical of the Republic of Chechnya due to the "children of war" achievement of childbearing age) and inobservance of optimal intergenetic interval contribute to the aforesaid phenomena. The analysis of pregnant women, women in labour and newborn children state of health shows that according to many characteristics it is worse than at the average in Russia. Feto-infantile losses in the Republics of Chechnya and Ingushetia are more than twice as high as in all over the Russian Federation. One of the most important conditions for the improvement of child-bearing age women and their children is increase of the efficacy of obstetrics and pediatric services in both Republics and family planning.